1989
DOI: 10.1073/pnas.86.2.651
|View full text |Cite
|
Sign up to set email alerts
|

Bis(benzyl)polyamine analogs inhibit the growth of chloroquine-resistant human malaria parasites (Plasmodium falciparum) in vitro and in combination with alpha-difluoromethylornithine cure murine malaria.

Abstract: A number of bis(benzyl)polyamine analogs were found to be potent inhibitors ofboth chloroquine-resistant and chloroquine-sensitive strains of the human malaria parasite Plasmodiumfalciparum in vitro (IC50 values = 0.2-14MM).Administration of one of the compounds, MDL 27695, which is N,N'-bis{3-[(phenylmethyl)aminolpropyl}-1,7-diaminoheptane (C6H5CH2NH(CH2)3NH(CH2)7NH(CH2)3NHCH2C6HS), at 10-15 mg/kg i.p. three times per day for 3 days in combination with 2% x-difluoromethylornithine (DFMO; eflornithine) (1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 26 publications
0
51
0
1
Order By: Relevance
“…Purine is released from red cells almost exclusively in the form ofhypoxanthine (23,24), and is thus susceptible to oxidation by xanthine oxidase present in the medium. Failure of 1 x 10-7 M chloroquine to abolish parasite growth is indicative of chloroquine resistance (31). Thus, we have demonstrated that a chloroquine-resistant strain ofP.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Purine is released from red cells almost exclusively in the form ofhypoxanthine (23,24), and is thus susceptible to oxidation by xanthine oxidase present in the medium. Failure of 1 x 10-7 M chloroquine to abolish parasite growth is indicative of chloroquine resistance (31). Thus, we have demonstrated that a chloroquine-resistant strain ofP.…”
Section: Resultsmentioning
confidence: 77%
“…These morphological changes are reversed by provision ofsufficient hypoxanthine to overcome the deficiency. Growth arrest at the same developmental stage is produced by a-difluoromethylornithine, an inhibitor of polyamine synthesis, which prevents DNA replication (31). In this case, normal maturation of schizonts is restored by putrescine rescue (32).…”
Section: Resultsmentioning
confidence: 99%
“…N,N'-Di-substituted tetraamines with the general formula RNH(CH2)XNH (CH2)YNH(CH2)NINHR have been reported to suppress the growth of several pathogenic protozoans (e.g., Leishmania donovani, Plasmodium falciparum, and Plasmodium berghei) in vitro and in infected animals (2)(3)(4) and could be suitable for exploring the role that polyamines and polyamine biosynthesis plays in T. cnuzi infection. In this work, we used two N,N'-bis(benzyl)-substituted polyamine analogs and studied their effects on T. cnuzi infectivity and replication using an in vitro model system of mammalian host cell infection.…”
mentioning
confidence: 99%
“…DFMO, a derivative of the amino acid ornithine, inhibits the enzyme irreversibly by an alkylation of its active site. A combination of DFMO and bis(benzyl)polyamines revealed a curative effect in rodent malaria [61]. Moreover DFMO reveals a more prominent role due to its effectiveness against Trypanosoma brucei gambiense, the agent of the West African Sleeping Sickness [62][63][64].…”
Section: Financial and Competing Interests Disclosurementioning
confidence: 99%
“…These molecules have to be detoxified. While the parasite possesses a variety of anti-oxidative defense mechanisms [9,[60][61][62][63], none of them addresses singlet oxygen. Recently it was demonstrated that PLP is involved in the protection against 1 O 2 in P. falciparum [58,64], which has been attributed to the catalysis of the plasmodial PLP synthase complex as validated by protein interference experiments using transgenically modified parasites [64].…”
mentioning
confidence: 99%